Implementation of Poverty Reduction Policies in the Province of North Sulawesi - Tamuntuan, Syenny F.; Pangkey, Itje; Bulo, Laurens (Technium Social Sciences Journal, 2025)
The purpose of the research was to find out, analyze and describe the coordination function mechanism in the Poverty Reduction Coordination Team (TKPK) of North Sulawesi Province in accelerating poverty alleviation in North Sulawesi and the determinant factors. This research used descriptive qualitative research methods. Data collection techniques used by researchers are observation, interviews and document studies. The informants in this study amounted to 16 people who were determined by purposive sampling technique. The indicators used in the coordination function mechanism are Organizational Structure, Coordination Process, Stakeholder Involvement, Program Implementation, and Monitoring and Evaluation. Meanwhile, the indicator for the determinant factor is Funding. The results showed that 1) The implementation mechanism of the poverty reduction coordination policy in North Sulawesi Province has not run optimally. Inappropriate program implementation was caused by the organizational structure, the involvement of relevant stakeholders, and the coordination process between team members that was not well established. Ineffective monitoring and evaluation resulted in obstacles that could not be anticipated and overcome; 2) Funding is one of the inhibiting factors in the implementation of poverty reduction coordination policies in North Sulawesi Province. There is a limited budget as a support system for the implementation of tasks that are not budgeted in the North Sulawesi Province Regional Budget (APBD).